PELAKSANAAN PRINSIP UTMOST GOOD FAITH UNTUK PRODUK ASURANSI PROPERTY ALL RISK - R. Muh Deddy Hanif Sardjito; Bayu Suganda; Bagus Suhendar; Rianita Natalia Sinaga; Reimond Hasangapan Mikkael Napitupulu (JURNAL LENTERA BISNIS, 2024)
This research aims to analyze the full application of the principle of good faith in Property All Risk (PAR) insurance products in Indonesia. This study explores how these principles are implemented by insurance companies and understood by policyholders, with a focus on potential challenges and misunderstandings that may arise. This research uses a qualitative approach using interviews and surveys of policyholders and insurance company representatives. Findings reveal that often there is a lack of clear communication from insurance companies regarding the terms and conditions of PAR policies. Many policyholders do not fully understand coverage and exclusions due to the complex legal language used in the policy. This lack of understanding can cause disputes during the claims process. This study is limited to the Indonesian insurance market and focuses on one type of insurance product only. This research suggests that insurance companies need to improve their communications strategies to ensure that policyholders fully understand the terms of their insurance policies. This can be done by simplifying the language used in the policy and providing a more comprehensive explanation during the policy issuance process.